Reconstruction of three-dimensional grain structure in polycrystalline iron via an interactive segmentation method - Feng, Min-nan; Wang, Yu-cong; Wang, Hao; Liu, Guo-quan; Xue, Wei-hua (International journal of minerals, metallurgy and materials, 2017)
Using a total of 297 segmented sections,we reconstructed the three-dimensional(3D) structure of pure iron and obtained the largest dataset of 16254 3D complete grains reported to date.The mean values of equivalent sphere radius and face number of pure iron were observed to be consistent with those of Monte Carlo simulated grains,phase-field simulated grains,Ti-alloy grains,and Ni-based super alloy grains.In this work,by finding a balance between automatic methods and manual refinement,we developed an interactive segmentation method to segment serial sections accurately in the reconstruction of the 3D microstructure;this approach can save time as well as substantially eliminate errors.The segmentation process comprises four operations:image preprocessing,breakpoint detection based on mathematical morphology analysis,optimized automatic connection of the breakpoints,and manual refinement by artificial evaluation.